Neuroanatomical Study of In-Vivo Brainstem Abnormalities in Autism Spectrum Disorder and Their Clinical Correlations - Pashmina Shaikh; Umbreen Bano; Samreen Memon; Shamshad Bano; Sameena Gul; Pirya (Pakistan Journal of Medicine and Dentistry)
Background: Autism Spectrum Disorder (ASD) is typically linked to dysfunction of the brainstem, interfering with sensory treatment and autonomic management. The study aimed at examining the structural changes in the brainstem of a rat model induced by propionic acid (PPA) and focused on neuroanatomy changes within the medulla and pons.